THE EFFECT OF AID ON GROWTH - Digdowiseiso, Kumba (Jurnal Sosial dan Humaniora, 2016)
This study tries to investigate the potential non-linearities in the aid â growth relationship as well as to explore whether aid is more effective in countries with good policies. By using the same dataset as Burnside and Dollar (2000) and Hansen and Tarp (2000, 2001), I find that a more positive impact of aid on growth in good policy environments is not a robust result in all models since it depends crucially on instruments. In addition, my study does not strongly confirm a non-linear relation between aid and growth in which it appears only in several GMM modelsÂ Keywords : Aid, Growth, and Policy